Life in the grave - Mohamed Ahmed Ibrahim,; Falah Hassan Mohammed,; Idan Hillel Ibrahim, (Islamic Sciences Journal, 2025)
ABSTRACT In this research, Imam Taj al-Din al-Hamawi (may Allah Almighty have mercy on him) focused on explaining the ruling on belief in the life of the grave, and that belief in this life is obligatory, and in the questioning of the dead by the two angels, and likewise belief in the torment and bliss of the grave is obligatory. He explained that the two angels who question the dead are: Munkar and Nakir, and that is after the soul of the dead is returned to his body, and after the questioning, the grave will be either a garden from the gardens of Paradise, or a pit from the pits of Hell. He provided evidence for that with correct transmitted evidence and decisive rational arguments.